MODIFIKASI ALAT BANTU PEMBELAJARAN MELEMPAR MENANGKAP DAN MEMUKUL BOLA DALAM HASIL BELAJAR PERMAINAN SOFTBALL - Aser Paul Nainggolan; Sejahtra Sejahtra (JURNAL CURERE, 2018)
The general objective of this research is to improve student outcomes through softball learning model by using a modification tool. In addition, this study was conducted to obtain in-depth information about the application of a softball game using the tool modification approach. Design research is action research. Subjects in this study were 32 eighth grade students in junior Mariana Medan. This research was conducted in six sessions of two cycles. Each cycle consisted of three sessions. The first cycle shows that through the actions of the students can motivate themselves. The first cycle of this result is 68.56 or 53 125% and that means finished. In the second cycle as a reflection of the first cycle also shows that action to motivate students. The results of the second cycle is 80 125, or 87.5%, and that means finished. Based on these results it can be concluded that: (1) Softball game using a modified approach to improve student learning outcomes tool, (2) Softball game using a modified approach the tool to motivate students and make students actively participate in the learning process.